Neural expression and regulation of NSSR1 proteins - Liu, Lei; Lin, Jun-Ji; Chen, Xianhua; Liu, Xuan; Xu, Ping (Neuroreport, 2003)
Neural salient serine-/arginine-rich protein 1 (NSSR1) is a newly identified SR protein that regulates pre-mRNA splicing. In the present study, we demonstrated the neural specialization of NSSR1 protein expression in humans and mice. Strong immunoreactive signals to NSSR1 were observed in mouse cerebral neurons, cerebellar Purkinje cells, pyramidal neurons in CA1, CA2 and CA3 regions of the hippocampus and granule cells in the dentate gyrus. In primarily cultured mouse neural progenitor cells (NPCs), at the undifferentiated status, NSSR1 transcripts were detected, but not the proteins. In comparison, in differentiated NPCs both NSSR1 transcripts and proteins were expressed and significantly up-regulated. The results suggest that NSSR1 is important in regulation of brain function and neural differentiation, possibly via regulating the neural-specific alternative splicing of genes.